2022
DOI: 10.14366/usg.20192
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the surgical reparability of large-to-massive rotator cuff tears by B-mode ultrasonography: a cross-sectional study

Abstract: To compare the predictability for surgical reparability of B-mode ultrasound and magnetic resonance imaging (MRI) in patients with large-to-massive rotator cuff tears (RCTs). MethodsThis was a cross-sectional study. Participants with large-to-massive RCTs who underwent arthroscopic repair were included. B-mode ultrasound and MRI were conducted prior to arthroscopic repair. B-mode ultrasound was used to evaluated the echogenicity of rotator cuff muscle using the Heckmatt scale. The intra-rater and inter-rater r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…When muscle thickness was measured at the scapular notch in both US and MRI, r = 0.76 [ 38 ]. Chen et al found medium to large effect sizes (r = 0.4–0.8) for correlating the large-to-massive rotator cuff tears and good predictive validity for surgical reparability between B-mode ultrasound and MRI findings [ 39 ]. Despite the promising findings on reliability in the examination of these measurements, the small sample size of patient populations and the lack of high quality and comprehensive quantifications of rotator cuff muscle tissue properties were not included.…”
Section: Resultsmentioning
confidence: 99%
“…When muscle thickness was measured at the scapular notch in both US and MRI, r = 0.76 [ 38 ]. Chen et al found medium to large effect sizes (r = 0.4–0.8) for correlating the large-to-massive rotator cuff tears and good predictive validity for surgical reparability between B-mode ultrasound and MRI findings [ 39 ]. Despite the promising findings on reliability in the examination of these measurements, the small sample size of patient populations and the lack of high quality and comprehensive quantifications of rotator cuff muscle tissue properties were not included.…”
Section: Resultsmentioning
confidence: 99%
“…The most important findings of the present study was that the diagnostic performance of the modified Patte classification system for tendon retraction, including the cut-off points for predicting reparability (medial one-fifth of the humeral head) and tendon healing after ARCR (medial one-third of the humeral head) in the Patte stage 2 area was excellent for reparability and acceptable for rotator cuff healing, with high measurement reliability. Previous literature indicates that retraction of the supraspinatus tendon is a significant predictive factor for reparability and postoperative rotator cuff integrity in ARCR [6,11,19,21,34,37]. The Patte classification has been widely used to classify tendon retraction, in which stage 3 retraction is a significant negative predictive factor for reparability and rotator cuff integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature indicates that retraction of the supraspinatus tendon is a significant predictive factor for reparability and postoperative rotator cuff integrity in ARCR [6, 11, 19, 21, 34, 37]. The Patte classification has been widely used to classify tendon retraction, in which stage 3 retraction is a significant negative predictive factor for reparability and rotator cuff integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations